Cost effectiveness evaluation of a rotavirus vaccination program in Argentina. Issue 42 (13th October 2015) - Martí, Sebastián García; Alcaraz, Andrea; Valanzasca, Pilar; McMullen, Mercedes; Standaert, Baudouin; Garay, Ulises; Lepetic, Alejandro; Gomez, Jorge
Abstract: Background: Rotavirus diarrhea is one of the most important vaccine-preventable causes of severe diarrhea in children worldwide. There are two live-attenuated virus vaccines licensed, Rotarix ® (RV1) a monovalent vaccine by GlaxoSmithKline and a pentavalent vaccine, RotaTeq ® (RV5), by Merck & Co., with similar results. This study aim was to evaluate the cost-effectiveness of the utilization of RV1 compared with RV5 in Argentina. Methods: A deterministic Markov model based on the lifetime follow up of a static cohort was used. Quality Adjusted Life Years (QALYs) as a measure of results, the perspective of the health care system and a 5% discount rate for health benefits and costs has been used. A review of the literature to obtain epidemiologic and resources utilization of rotavirus diarrhea was performed. The sources used to estimate epidemiologic parameters were the National Health Surveillance System, the national mortality statistics and national database of hospital discharges records. Costs were obtained from different health subsectors and are expressed in local currency. Results: Both vaccination alternatives were less costly and more effective than the strategy without vaccination (total costs $ 69, 700, 645 and 2575 total QALYs lost). When comparing RV1 vs. RV5, RV1 was less expensive ($ 60, 174, 508 vs. $ 67, 545, 991 total costs) and more effective (1105 vs. 1213 total QALYs lost) than RV5, RV1 being therefore a dominating strategy. Probabilistic sensitivity analysis showed results to be robust with a 100% probability of being cost-effective at a WTP threshold of 1 GDP per capita when comparing the RV1 vs. no vaccination. Conclusion: Both RV1 and RV5 schedules dominate the no vaccination strategy and RV5 was dominated by RV1. This information is a valuable input regarding the incorporation of this kind of vaccines into the national vaccination programs.